Health information services: Engaging women in cervical cancer screening awareness in Nigeria. (October 2019) - Osuchukwu, Ngozi P.; Ukachi, Ngozi B.
Around the world, a woman dies of cervical cancer every two minutes. In Nigeria, it is the second leading cause of cancer deaths, which could be avoided with proper access to health information. This mixed methods study, which employs a questionnaire, interviews, observations and discussion, examined women's awareness on cervical cancer, screening status, sources, attitude and willingness, factors deterring them from being screened, and lessons learnt. Screening was done using visual inspection with acetic acid (VIA). The study involved two librarians, two medical doctors, a pharmacist and a laboratory scientist: 90 women participated in the cervical screening exercise in non-standard settings – an e-library and a cathedral. It was discovered that 90% of the women had never been screened. Thus, if the women are not sensitized on cervical cancer they may never go for screening and more casualties will be recorded. The paper concludes with recommendations and a call to action for all, especially librarians.